2015
DOI: 10.1097/mpg.0000000000000850
|View full text |Cite
|
Sign up to set email alerts
|

School Attendance in Children With Functional Abdominal Pain and Inflammatory Bowel Diseases

Abstract: FAP has a significant impact on school attendance and functioning similar to IBD. These findings show that significant psychosocial and academic difficulties are faced not only by children with chronic diseases like IBD but also by children with FAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 23 publications
5
47
0
4
Order By: Relevance
“…The findings highlighted absenteeism and the negative effect of pain on the ability of students to engage in certain activities as the most important problems that children who have chronic pain face. This is consistent with other studies reporting these as important difficulties in young people with chronic pain . Future researchers should look at developing and evaluating strategies that teachers may use to help their students experiencing chronic pain cope with absenteeism.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings highlighted absenteeism and the negative effect of pain on the ability of students to engage in certain activities as the most important problems that children who have chronic pain face. This is consistent with other studies reporting these as important difficulties in young people with chronic pain . Future researchers should look at developing and evaluating strategies that teachers may use to help their students experiencing chronic pain cope with absenteeism.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with other studies reporting these as important difficulties in young people with chronic pain. 7,26,27 Future researchers should look at developing and evaluating strategies that teachers may use to help their students experiencing chronic pain cope with absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Children with chronic pain often significantly decrease the amount of time spent in activities with peers, including sports and other extracurricular activities [1]. Children who miss significant periods of school due to pain may experience loss of friendships, feel more isolated, are less well-liked, and are less socially accepted than their healthy peers [3,89]. Across a variety of studies, children with chronic pain have reported having fewer friends, were more likely to be victimized by peers, were more isolated, and were evaluated as less likable than healthy peers [90].…”
Section: Current Status Of the Literature On Risk Factors For Pedimentioning
confidence: 99%
“…Other research has also confirmed that, for example, functional abdominal pain in adolescents can have an impact on various school activities, for instance, gym classes and after-school activities, such as afternoon group classes (Assa, Ish-Tov, Rinawi, & Shamir, 2015). The school nurses wanted to normalize the situation, and the school work can be improved when the intervention focuses on a return to functioning (Claar, Kaczynski, Minster, McDonald-Nolan, & LeBel, 2013).…”
Section: Discussionmentioning
confidence: 94%